Scenario-driven spatiotemporal modeling of nonlinear drought dynamics and systemic risks using CMIP6 data - Habib Ullah; Fathia M. Al Samman; Ijaz Hussain; Rizwan Niaz; Hefa Cheng; Nafisa A. Albasheir; Mohammed M.A. Almazah (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Monitoring drought occurrence through a count-based statistical modeling - Rizwan Farooq; Maysaa Elmahi Abd Elwahab; Rizwan Niaz; Hefa Cheng; Mhassen E.E. Dalam; Mohammed M.A. Almazah; Ijaz Hussain (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Enhanced activation of peracetic acid by Cu2O under sunlight through coordination environment regulation: Improved charge separation and peracetic acid adsorption/complexation via uncoordinated Cu atoms - Jinpeng Wang; Yuqing Cao; Yi Han; Xiaoding Huang; Xiaoyong Wu; Hefa Cheng; Dejin Wang (Chemical Engineering Journal, 2026)

Crystal structure manipulation for enhanced activity of MnO2 in sunlight-mediated peracetic acid activation: Phase-dependent charge separation and activation mechanisms - Jinpeng Wang; Yuqing Cao; Qingshan Li; Xingwang Wu; Xu Yang; Hefa Cheng; Dejin Wang (Journal of Cleaner Production, 2026)

Assessing drought dynamics across climatic zones using parametric and entropy copula models - Muhammad Owais Khan; Luca Di Persio; Rizwan Niaz; Hefa Cheng; Laila A. Al-Essa; Hanen Louati; Mhassen. E. E. Dalam (Stochastic Environmental Research and Risk Assessment, 2026)

Hydrobiogeochemical impacts of water sealing on acid mine drainage in karst regions - Lei Song; Peng Liu; Chao Li; Haili Zhang; Jie Yan; Yuhui Liu; Zengping Ning; Yizhang Liu; Jing Sun; Hefa Cheng; Chengshuai Liu (Journal of Hydrology, 2026)

Assessment of Climatological Trends, Spatial Distribution and Driving Forces of Extreme Daily Precipitation Events - Habib Ullah; Rizwan Niaz; Ijaz Hussain; Huda M. Alshanbari; Mohammed M. A. Almazah; Hefa Cheng (Pure and Applied Geophysics, 2026)

Improving drought risk assessment using advanced statistical approaches - Rizwan Farooq; Rizwan Niaz; Ijaz Hussain; Hefa Cheng; Huda M. Alshanbari; Hanen Louati; Shreefa O. Hilali (Acta Geophysica, 2026)

Mathematical and Data-Driven Modeling of Hybrid Probabilistic Models for Monthly Drought Monitoring - Hamza Khalid; Rizwan Niaz; Luca Di Persio; Mohammed M. A. Almazah; Hefa Cheng; Fathia Moh. Al Samman; Mansour Almazroui (Acta Geophysica, 2026)

Design and fabrication of Z-scheme BWB/FeVO4/NiBi2O4 heterojunction with bridged biochar as an electron mediator for antibiotic degradation - Gopal Rajesh; Juying Li; Hefa Cheng (Journal of Environmental Chemical Engineering, 2026)

Integrating climatic and topographic drivers in a poisson-GEE framework for modelling drought dynamics - Rizwan Farooq; Maysaa Elmahi Abd Elwahab; Rizwan Niaz; Hefa Cheng; Mhassen. E. E. Dalam; Mohammed M. A. Almazah; Ijaz Hussain (Theoretical and Applied Climatology, 2026)

Crucial role of in-situ formed Mn(III) species in pollutant degradation by persulfate activated with Fe-Mn binary oxide-modified biochar - Xian Li; Hefa Cheng (Water Research, 2026)

A Bayesian Framework for Spatiotemporal Analysis of Meteorological Drought Dynamics - Rizwan Farooq; Rizwan Niaz; Ijaz Hussain; Mohammed M. A. Almazah; Shreefa O. Hilali; Hefa Cheng (Pure and Applied Geophysics, 2026)

Bayesian geostatistical insights into seasonal variability and spatiotemporal structure of precipitation - Fazal Din; Mohammed M. A. Almazah; Rizwan Niaz; Hefa Cheng; Fathia Moh. Al Samman; Shreefa O. Hilali (Acta Geophysica, 2026)

Integrating time–space dynamics for meteorological drought monitoring and trend analysis - Zahid Shah; Rizwan Niaz; Mohammed M. A. Almazah; Hefa Cheng; Fathia Moh. Al Samman; Shreefa O. Hilali (Acta Geophysica, 2025)

Modeling meteorological drought across scales with regional and global climate indicators - Muhammad Ilyas; Rizwan Niaz; Hefa Cheng; Luca Di Persio; Maysaa Elmahi Abd Elwahab; Ali Danandeh Mehr; Ijaz Hussain (Theoretical and Applied Climatology, 2025)

Quantification of per- and polyfluoroalkyl substances (PFASs) in aqueous film-forming foam (AFFF)-impacted water: Comparisons between methodologies and laboratories - Chuhui Zhang; Nicholas Gonda; Ashley N. Kimble; Eric Redman; Cynthia M. Grim; Siwei Gu; Anthony Bednar; Karen Dahl; Chenyi Yuan; Yue Zhi; Hefa Cheng; Christopher P. Higgins (Journal of Hazardous Materials, 2025)

Corrigendum to “A novel slow-release citric acid for enhancing the phytoremediation of uranium-contaminated soil by Indian mustard (Brassica juncea L.) and ryegrass (Lolium perenne L.)” [J. Clean. Prod. 519 (2025) 145973] - Kai Yang; Yu Xue; Runchuan Fan; Litang Hu; Naifu Jin; Aizhong Ding; Hefa Cheng (Journal of Cleaner Production, 2025)

Kinetics and potential risk of heavy metal release from commercial organic fertilizers in northern China - Yafeng Wang; Teresa J. Cheng; Hefa Cheng (Environmental Pollution, 2025)

Influence of long-term inorganic fertilization and straw incorporation on soil organic carbon: Roles of enzyme activity, labile organic carbon fractions, soil aggregates, and microbial traits - Ning Wang; Zhipin Ai; Qiuying Zhang; Peifang Leng; Yunfeng Qiao; Zhao Li; Chao Tian; Hefa Cheng; Gang Chen; Fadong Li (Agriculture, Ecosystems & Environment, 2025)

A novel slow-release citric acid for enhancing the phytoremediation of uranium-contaminated soil by Indian mustard (Brassica juncea L.) and ryegrass (Lolium perenne L.) - Kai Yang; Yu Xue; Runchuan Fan; Litang Hu; Naifu Jin; Aizhong Ding; Hefa Cheng (Journal of Cleaner Production, 2025)

Occurrence and Risk Assessment of Microplastics Pollution in the World’s Longest Natural Beach, Cox’s Bazar, Bangladesh - Tariqul Islam; Hefa Cheng (Water, Air, & Soil Pollution, 2025)

Investigating the Toxic Impacts of Various Arsenic Compounds on Hydroponics Lettuce (Lactuca sativa L.): Biomass, Arsenic Accumulation and Species Distribution - Hui Feng; Yingying Zhang; Kuan Fang; Yuanan Hu; Hefa Cheng (Water, Air, & Soil Pollution, 2025)

Distinct assembly mechanisms of the abundant and rare bacterial taxa in plateau habitats - Xiaojie Wang; Hefa Cheng (Applied Soil Ecology, 2025)

Generally Reduced Sink Capacity of Upland Soils for Atmospheric Methane Over the Past Three Decades (1993–2022) - Zhaoxin Li; Yanmeng Shang; Chao Wang; Jinyang Wang; Xiaobo Liu; Fadong Li; Gang Chen; Hefa Cheng; Jianwen Zou; Shuwei Liu (Global Change Biology, 2025)
Upland soils act as the second largest and the only manageable sink of atmospheric methane (CH 4 ). Quantifying spatiotemporal patterns of the net CH 4 exchange between upland soils and atmosphere is critical for refining global CH 4 budget estimates and developing climate mitigation strategies. However, the global CH 4 budget in upland soils remains highly uncertain due to incomplete understanding of the shifts in the source or sink role of upland soils for CH 4 under climate change. In this study, we generated high‐resolution global maps of CH 4 fluxes from upland soils by integrating field CH 4 flux measurement data spanning over the period of 1993–2022 using machine learning models. Collectively, upland soils exhibited a generally reduced sink capacity for atmospheric methane over the past three decades. Cropping uplands presented a shift from a weak sink to a source, and grassland soils changed from a sink to a strong source of CH 4 . The sink capacity of forest soils for CH 4 sharply decreased by 68.8% over the past three decades, while tundra upland soils acted as a consistent source of CH 4 , with a decrease of 55.3% since 1993. The combined effects of changes in precipitation and temperature can explain more than 70% of spatiotemporal variations of CH 4 fluxes in upland soils. Our findings provide a new perspective on the spatiotemporal patterns of CH 4 fluxes in global upland soils, which update the role of upland soils in the global CH 4 budget, particularly as a potential CH 4 sink.

Fractal spatial heterogeneity of trace element abundance in pristine surface soils: Implications for pollution assessment and source apportionment - Yiming Huang; Yuanan Hu; Hefa Cheng; Shu Tao (Environmental Pollution, 2025)

Characterization and risk assessment of microplastics in shoreline sediments of the Yellow River Delta - Tariqul Islam; Hefa Cheng (Marine Environmental Research, 2025)

Variation of bacterial community diversity and composition in saline-alkali soils reclaimed with flood irrigation and crop cultivation is driven by salinity and edaphic factors - Yue Yin; Grace M. Cheng; Hefa Cheng (Science of The Total Environment, 2025)

Unique role of Mn(II) in enhancing electro-oxidation of organic pollutants on anodes with low oxygen evolution potential at low current density - Erdan Hu; Yuhua Ye; Bing Wang; Hefa Cheng (Journal of Hazardous Materials, 2024)

Existence and fate of microplastics in terrestrial environment: A global fretfulness and abatement strategies - Tariqul Islam; Hefa Cheng (Science of The Total Environment, 2024)

Radiological risk and impact on soil microbial diversity of radionuclides in agricultural topsoils downstream of a decommissioned hydrometallurgical uranium plant - Kai Yang; Yu Xue; Runchuan Fan; Naifu Jin; Junfeng Dou; Hefa Cheng (Journal of Environmental Management, 2024)

Impacts of nitrogen (N), phosphorus (P), and potassium (K) fertilizers on maize yields, nutrient use efficiency, and soil nutrient balance: Insights from a long-term diverse NPK omission experiment in the North China Plain - Ning Wang; Zhipin Ai; Qiuying Zhang; Peifang Leng; Yunfeng Qiao; Zhao Li; Chao Tian; Hefa Cheng; Gang Chen; Fadong Li (Field Crops Research, 2024)

Sources, bioaccessibility and health risk of heavy metal(loid)s in the particulate matter of urban areas - Yuxuan Ren; Yuanan Hu; Hefa Cheng (Science of The Total Environment, 2024)

Insights into sunlight-driven transformation of tetracycline by iron (hydr)oxides: The dominating role of self-generated hydrogen peroxide - Shiwen Li; Jianming Pang; Wei Han; Ting Chang; Lingen Luo; Xian Li; Jue Liu; Hefa Cheng (Water Research, 2024)

Health risk assessment from inhalation exposure to indoor formaldehyde: A systematic review and meta-analysis - Amir Hossein Khoshakhlagh; Mahdiyeh Mohammadzadeh; Safiye Ghobakhloo; Hefa Cheng; Agnieszka Gruszecka-Kosowska; Jasper Knight (Journal of Hazardous Materials, 2024)

Influences of shallow groundwater depth on N2O diffusion along the soil profile of summer maize fields in North China Plain - Zhao Li; Xurun Li; Qiuying Zhang; Fadong Li; Yunfeng Qiao; Shanbao Liu; Peifang Leng; Chao Tian; Gang Chen; Hefa Cheng (Science of The Total Environment, 2024)

Endocrine disrupting effects of parabens in zebrafish (Danio rerio): New insights from transcriptomics, metabolomics, and molecular dynamics simulation - Fang Wei; Huifeng Yue; Binjie Wang; Hefa Cheng; Nan Sang (Chemosphere, 2024)

Environmental performance of unfired bricks produced from co-disposal of mine tailings and municipal solid waste incineration fly ash based on comprehensive leaching tests - Ping Wang; Jiangshan Li; Yuanan Hu; Hefa Cheng (Environmental Pollution, 2024)

Non-negligible N2O emission hotspots: Rivers impacted by ion-adsorption rare earth mining - Wang Shu; Qiuying Zhang; Joachim Audet; Zhao Li; Peifang Leng; Yunfeng Qiao; Chao Tian; Gang Chen; Jun Zhao; Hefa Cheng; Fadong Li (Water Research, 2024)

The leaching behavior of heavy metal from contaminated mining soil: The effect of rainfall conditions and the impact on surrounding agricultural lands - Fei Wang; Wei Li; Hao Wang; Yuanan Hu; Hefa Cheng (Science of The Total Environment, 2024)

Potential risk, leaching behavior and mechanism of heavy metals from mine tailings under acid rain - Wei Li; Yu Deng; Hao Wang; Yuanan Hu; Hefa Cheng (Chemosphere, 2024)

Adsorptive and photocatalytic degradation of imidacloprid pesticide from wastewater via the fabrication of ZIF-CdS/Tpy quantum dots - Homa Targhan; Aram Rezaei; Alireza Aliabadi; Huajun Zheng; Hefa Cheng; Tejraj M. Aminabhavi (Chemical Engineering Journal, 2024)

Recyclable MXene-bridged Z-scheme NiFe2O4/MXene/Bi2WO6 heterojunction with enhanced charge separation for efficient sonocatalytic removal of ciprofloxacin - Guowei Wang; Hefa Cheng (Science of The Total Environment, 2023)

Sources, impacts, factors affecting Cr uptake in plants, and mechanisms behind phytoremediation of Cr-contaminated soils - Sadeeq Ullah; Qingling Liu; Shiyong Wang; Amin Ullah Jan; Hafiz M. Adeel Sharif; Allah Ditta; Gang Wang; Hefa Cheng (Science of The Total Environment, 2023)

Household energy stacking and structures in Pakistan – Results from a multiple-energy study in Azad Kashmir and Punjab - Xiaoqiao Jiao; Rui Xiong; Zhihan Luo; Yaojie Li; Hefa Cheng; Audil Rashid; Guofeng Shen; Shu Tao (Journal of Environmental Sciences, 2023)

Characterization of atmospheric mercury from mercury-added product manufacturing using passive air samplers - Qing Luo; Yuxuan Ren; Zehang Sun; Yu Li; Bing Li; Sen Yang; Wanpeng Zhang; Frank Wania; Yuanan Hu; Hefa Cheng (Environmental Pollution, 2023)

Seasonal variations and driving mechanisms of CO2 fluxes over a winter-wheat and summer-maize rotation cropland in the North China plain - Zewei Yue; Zhao Li; Guirui Yu; Zhi Chen; Peili Shi; Yunfeng Qiao; Kun Du; Chao Tian; FengHua Zhao; Peifang Leng; Zhaoxin Li; Hefa Cheng; et al. (Agricultural and Forest Meteorology, 2023)

Visible-light induced tetracycline degradation catalyzed by dual Z-scheme InVO4/CuBi2O4/BiVO4 composites: The roles of oxygen vacancies and interfacial chemical bonds - Jue Liu; Shiwen Li; Can Meng; Jing Sun; Xian Li; Yuanan Hu; Hefa Cheng (Chemical Engineering Journal, 2023)

Soil heavy metal(loid) pollution and health risk assessment of farmlands developed on two different terrains on the Tibetan Plateau, China - Yafeng Wang; Hefa Cheng (Chemosphere, 2023)

Mn-modified biochars for efficient adsorption and degradation of cephalexin: Insight into the enhanced redox reactivity - Xian Li; Hefa Cheng (Water Research, 2023)

Insights on the assembly processes and drivers of soil microbial communities in different depth layers in an abandoned polymetallic mining district - Yue Yin; Xiaojie Wang; Yuanan Hu; Fadong Li; Hefa Cheng (Journal of Hazardous Materials, 2023)

Environmental fate and ecological impact of the potentially toxic elements from the geothermal springs - Yafeng Wang; Hefa Cheng (Environmental Geochemistry and Health, 2023)

Indoor air pollution from the household combustion of coal: Tempo-spatial distribution of gaseous pollutants and semi-quantification of source contribution - Lifan Qin; Mengkun Zhai; Hefa Cheng (Science of The Total Environment, 2023)

Soil CO2 emission reduction with no-tillage and medium nitrogen fertilizer applications in semi-humid maize cropland in North China Plain - Zhaoxin Li; Qiuying Zhang; Fadong Li; Zhao Li; Yunfeng Qiao; Kun Du; Zewei Yue; Chao Tian; Peifang Leng; Hefa Cheng; Gang Chen (European Journal of Agronomy, 2023)

Environmental and human health impacts of geothermal exploitation in China and mitigation strategies - Yuanan Hu; Hefa Cheng; Shu Tao (Critical Reviews in Environmental Science and Technology, 2023)

Direct Z-scheme In2O3/AgI heterojunction with oxygen vacancies for efficient molecular oxygen activation and enhanced photocatalytic degradation of tetracycline - Jue Liu; Can Meng; Xinyu Zhang; Senyu Wang; Kuan Duan; Xian Li; Yuanan Hu; Hefa Cheng (Chemical Engineering Journal, 2023)

Influence of hydrogeological and geochemical parameters on N2O in the groundwater in the irrigation area of lower reaches of Yellow River - Zhao Li; Qiuying Zhang; Zhaoxin Li; Shanbao Liu; Chao Tian; Yunfeng Qiao; Hefa Cheng; Gang Chen; Qiuhong Tang; Fadong Li (Journal of Hydrology, 2023)

The recycling potential of unregulated waste electrical and electronic equipment in China: Generation, economic value, and cost-benefit analysis - Bingbing Sun; Beibei Li; Shexia Ma; Ming Zhu; Chenyin Dong; Mingdeng Xiang; Hefa Cheng; Yunjiang Yu (Journal of Cleaner Production, 2023)

Toxic effects of cadmium on the physiological and biochemical attributes of plants, and phytoremediation strategies: A review - Yanliang Li; Shafeeq Ur Rahman; Zhixin Qiu; Sher Muhammad Shahzad; Muhammad Farrakh Nawaz; Jianzhi Huang; Sadiq Naveed; Lei Li; Xiaojie Wang; Hefa Cheng (Environmental Pollution, 2023)

Effects of physical aging processes on the bioavailability of heavy metals in contaminated site soil amended with chicken manure and wheat straw biochars - Kai Yang; Xilong Wang; Hefa Cheng; Shu Tao (Environmental Pollution, 2023)

Responses of soil CO2 emissions to tillage practices in a wheat maize cropping system: A 4-year field study - Zhaoxin Li; Qiuying Zhang; Zhao Li; Yunfeng Qiao; Kun Du; Zewei Yue; Chao Tian; Peifang Leng; Hefa Cheng; Gang Chen; Fadong Li (Field Crops Research, 2023)

Facile synthesis of a novel recyclable dual Z-scheme WO3/NiFe2O4/BiOBr composite with broad-spectrum response and enhanced sonocatalytic performance for levofloxacin removal in aqueous solution - Guowei Wang; Hefa Cheng (Chemical Engineering Journal, 2023)

Climate controls over phenology and amplitude of net ecosystem productivity in a wheat-maize rotation system in the North China plain - Zewei Yue; Zhao Li; Guirui Yu; Zhi Chen; Peili Shi; Yunfeng Qiao; Kun Du; Chao Tian; FengHua Zhao; Peifang Leng; Zhaoxin Li; Hefa Cheng; et al. (Agricultural and Forest Meteorology, 2023)

Responses of soil greenhouse gas emissions to no-tillage: A global meta-analysis - Zhaoxin Li; Qiuying Zhang; Zhao Li; Yunfeng Qiao; Kun Du; Zewei Yue; Chao Tian; Peifang Leng; Hefa Cheng; Gang Chen; Fadong Li (Sustainable Production and Consumption, 2023)

Distinct distribution patterns of the abundant and rare bacteria in high plateau hot spring sediments - Xiaojie Wang; Yue Yin; Zhiqiang Yu; Guofeng Shen; Hefa Cheng; Shu Tao (Science of The Total Environment, 2023)

Solidification and stabilization of Pb–Zn mine tailing with municipal solid waste incineration fly ash and ground granulated blast-furnace slag for unfired brick fabrication - Ping Wang; Jiangshan Li; Yuanan Hu; Hefa Cheng (Environmental Pollution, 2023)

Soil bacterial community structure in the habitats with different levels of heavy metal pollution at an abandoned polymetallic mine - Yue Yin; Xiaojie Wang; Yuanan Hu; Fadong Li; Hefa Cheng (Journal of Hazardous Materials, 2023)

Distribution of microbial communities in seasonally frozen soil layers on the Tibetan Plateau and the driving environmental factors - Xiaojie Wang; Zhiqiang Yu; Guofeng Shen; Hefa Cheng; Shu Tao (Environmental Science and Pollution Research, 2023)

Opportunity and challenges in large-scale geothermal energy exploitation in China - Yuanan Hu; Hefa Cheng; Shu Tao (Critical Reviews in Environmental Science and Technology, 2022)

Source apportionment based on the comparative approach of two receptor models in a large-scale region in China - Mohamed Lamine Diakite; Yuanan Hu; Hefa Cheng (Environmental Science and Pollution Research, 2021)

Role of silicon on root morphological characters of wheat (Triticum aestivum L.) plants grown under Cd-contaminated nutrient solution - Shafeeq Ur Rahman; Qi Xuebin; Ghulam Yasin; Hefa Cheng; Faisal Mehmood; Muhammad Zain; Muhammad Shehzad; Muhammad Irfan Ahmad; Luqman Riaz; Abdur Rahim; Saeed Ur Rahman (Acta Physiologiae Plantarum, 2021)

Comparison of soil heavy metal pollution caused by e-waste recycling activities and traditional industrial operations - Kailing He; Zehang Sun; Yuanan Hu; Xiangying Zeng; Zhiqiang Yu; Hefa Cheng (Environmental Science and Pollution Research, 2017)

Sorption of chlorophenols on microporous minerals: mechanism and influence of metal cations, solution pH, and humic acid - Hui Yang; Yuanan Hu; Hefa Cheng (Environmental Science and Pollution Research, 2016)

Assessing heavy metal pollution in the surface soils of a region that had undergone three decades of intense industrialization and urbanization - Yuanan Hu; Xueping Liu; Jinmei Bai; Kaimin Shih; Eddy Y. Zeng; Hefa Cheng (Environmental Science and Pollution Research, 2013)

Improving China’s water resources management for better adaptation to climate change - Hefa Cheng; Yuanan Hu (Climatic Change, 2012)

Volatile Flavor Compounds in Yogurt: A Review - Hefa Cheng (Critical Reviews in Food Science and Nutrition, 2010)